Effects of pica practice on oral bacteriome and mycobiome profiles among pregnant women: A comparative study - Brenda A. Z. Abu; Lanxin Zhang; Robert Beblavy; Yan Wu; Xingyi Lu; Kevin Fiscella; Michael B. Sohn; Jin Xiao (PLoS ONE, 2026)
Introduction Pica, the excessive craving and consumption of non-food substances such as clay, and ice, is common among pregnant women but may pose risks for oral and systemic infections. Objective Assessed the comparative effect of pica practice on the oral microbiome (bacteriome and mycobiome) profiles of pregnant women. Methods A cross-sectional study was conducted in Upstate New York among pregnant women. Demographic, socioeconomic, pica practices (current and past), and oral hygiene practices were collected via questionnaires. The medical history of anemia was self-reported and verified using electronic records. A calibrated dentist assessed dental caries, periodontal status, and a comprehensive oral examination (plaque index, bleeding on probing). Oral samples (saliva and supragingival plaque) and pica samples were collected for the microbiome for Genomic DNA using I6S rRNA and ITS DNA sequencing and analyzed using linear regression with and without anemia as a covariate. Results Of the 20 pregnant women in the study, 17 were minority women (75% non-white). The mean age of participants was 29 years, and 29 weeks of gestational age. Eight participants (40.0%) reported practicing pica, and six provided samples, namely ice (and popsicles), and chalk. Streptococcus , Actinomyces , and Prevotella dominated in both saliva and plaque samples, but the microbial compositions differed. Between the pica and the non-pica groups, two differentially abundant (DA) bacterial taxa were identified in saliva samples with and without anemia namely Oribacterium sinus (p < 0.05). In plaqueseven identical DA bacterial taxa including Prevotella nigrescens were seen except for Leptotrichia goodfellowii , which was unique to when anemia was controlled for ( p < 0.05). Network analysis showed the co-occurrence of Candida albicans and Lactobacillus in the pica group. Conclusion Pica practice was associated with specific oral taxa abundance change in saliva and supragingival plaque, reflecting distinct microbiome distributions. In the regression model, including anemia as a covariate had almost no impact on the overall DA results. These findings are preliminary, indicating that future large prospective cohort studies are warranted to thoroughly assess the impact of pica practice on oral flora.